Implementasi Pemecahan Transmisi Data Citra pada Protokol Lora - Ahmad Nasrul Illahi; Adhitya Bhawiyuga; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Lora is one of the Low Power Wide Area (LPWA) networks that allows a device that has a small amount of energy to be distributed over a large area so as to create a network that is interconnected with each other. One of the challenges in LoRa is the packet payload capacity that is sent through this protocol. The LoRa protocol has a packet payload capacity of between 51 byte and 222 byte, so it has limitations in sending data with large file sizes such as image data. From this explanation, this research focuses on implementing a data splitting mechanism to overcome these deficiencies. In this study, the image data splitting process will be carried out in the end node, then the image data fragments will be merged back inside the gateway and the image will be displayed through the server. The test results obtained from the largest latency which is at a distance of 100 meters by 10 seconds, while the lowest latency is at a distance of 10 meters by 1 second. In addition to the latency measurement, there is a success ratio measurement for sending data fragments that produces a maksimal value of 100% and the lowest value of 20% at a distance of 100 meters. In addition, there is an RSSI measurement that is measured and produces the lowest value of -88 dbm and the highest -112 dbm.